The Effect of the STAD Type Cooperative Learning Model with the Help of Crossword Worksheet on Biology Learning Outcomes, especially the Cognitive Domain - Zb, Aminah; Ananda, Rizki; Mensah, Bismark (International Journal of Education and Teaching Zone, 2022)
This study aims to determine the effect of the STAD-type cooperative model with the help of Crossword Puzzles on students' biology learning outcomes, especially on Development and Growth material in terms of Cognitive aspects. The population in this study amounted to 5 classes, and a sample of 2 classes was taken randomly. The study was conducted in two classes which were grouped as experimental class and control class. In the experimental class, learning is carried out using a STAD-type cooperative model with the help of crossword puzzle worksheets, while in the control class, learning is carried out using a conventional model research data obtained from the test of learning outcomes for cognitive aspects. Student learning outcomes on cognitive aspects were analyzed by t-test. The results of data analysis show that the learning outcomes of cognitive domain biology students whose learning uses the STAD-type cooperative model with the help of crossword puzzle worksheets are higher than students whose learning uses the conventional model.